Study of cocrystallization between ibuprofen and glutaric acid via slow evaporation technique - Rahamat, Farah Alia (2017)
Active Pharmaceutical Ingredients (APIs) are known as active chemical agent that delivers the effect of the substances into the body such as pharmaceutical drugs. These drugs can be administered through oral ingestion into the body system of the patients. However, less than 40% of these drugs are water soluble, particularly ibuprofen which is categorized in BSC Class II drugs. Thus, cocrystallization has emerged as one of the novel ways to overcome this dilemma. Pharmaceutical cocrystal can be defined as multi-component crystal that consists of two or more solid compounds under ambient condition where at least one of the compound is neutral API and the coformer is pharmaceutically accepted ion or molecules. Cocrystallization has become a promising method used nowadays to enhance the solubility, bioavailability and stability of most of the APIs. Cocrystallization between ibuprofen (API) and glutaric acid (coformer) has been studied in this research paper through slow evaporation technique with two solvents which are ethanol and propanol. The cocrystallization was conducted with nine different molar ratios starting from 0.5 to 4.5 moles with step size of 0.5. Pure ibuprofen and glutaric acid were mixed and heated until they were completely dissolved before being left at room temperature for slow evaporation process. The cocrystal characterizations were performed using four different equipment which are optical microscope (OM), Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and X-ray Diffraction (XRD). Based on the results obtained, glutaric acid is a suitable coformer for ibuprofen to undergoes cocrystallization technique. However, it was revealed that lower molar ratios are more suitable for this process both for ethanol and propanol (within range 0.5 – 3.0). Therefore, it can be concluded that glutaric appears to be a suitable coformer for ibuprofen in lower molar ratios.